Cumae und Paestum, Italien: Hellenistische Heiligtümer in Campanien - Wolf, Markus (e-Forschungsberichte des DAI, 2023)
In the context of a wider study of Hellenistic altars and sanctuaries in Campania the temple of Apollo at Cuma and a group of hellenistic tempietti in the Northwest of the southern sanctuary at Paestum were explored. At Cuma the temple of the early imperial period, the main building phase, could be reconstructed but also a hellenistic, samnitic peripteros with elements in stone which were reused in the roman building could be distinguished. The ionic temple of Cuma enriches our image of monumental ionic architecture in central and southern Italy. The hellenistic Amphiprostylos of Paestum however could be reconstructed with a tetrastyle doric frontfacade.